Analysis of Performance Degradation Introduced by Radome for High-Precision GNSS Antenna. (2nd June 2019) - Liu, Jinyuan; Li, Lixun; Zuo, Yong; Chen, Huaming; Ni, Shaojie
Abstract : High-precision global navigation satellite system (GNSS) antennas employed on the fixed ground station are usually equipped with radomes, which are potential in yielding degradation of key parameters of antenna such as axial ratio and gain. This paper presents a study on the deterioration of high-precision GNSS antenna caused by the radome using electrically EM simulations including comparison of different geometries, materials, and heights of radome. Based on the study, an optimized radome model is proposed to minimize the axial ratio and gain degradation of antenna. Finally, a prototype of proposed radome is fabricated and measured. A good agreement between simulated and measured results evidently illustrates that the geometry, material, and height of radome are set appropriately.